2022
DOI: 10.1038/s41598-022-17560-x
|View full text |Cite
|
Sign up to set email alerts
|

Socio-psychological determinants of Iranian rural households' adoption of water consumption curtailment behaviors

Abstract: Dealing with a growing population and a shortage of drinking water is a major challenge for politicians and planners. A key factor in ensuring a sustainable water supply is water conservation at the household level, which can increase productivity and save water resources. Therefore, promoting water consumption curtailment behavior will contribute significantly to reducing the global water crisis, especially in arid and semi-arid regions. Water consumption curtailment behaviors depend on individuals’ encourage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 106 publications
2
12
0
Order By: Relevance
“…The results indicated that the model used in the context of behavioral intentions towards forest protection was very successful and unique, because the figure of variance explained by extended TPB was 78.7%. In the analysis of this result, it can be said that using the TPB model in the field of forest protection compared to the results of other studies on different issues such as food waste ( Soorani and Ahmadvand, 2019 ), organic agriculture ( Yazdanpanah and Forouzani, 2015 ), water saving ( Savari et al, 2022a ), etc. has been more successful because the amount of explained variance in present study is higher than them.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The results indicated that the model used in the context of behavioral intentions towards forest protection was very successful and unique, because the figure of variance explained by extended TPB was 78.7%. In the analysis of this result, it can be said that using the TPB model in the field of forest protection compared to the results of other studies on different issues such as food waste ( Soorani and Ahmadvand, 2019 ), organic agriculture ( Yazdanpanah and Forouzani, 2015 ), water saving ( Savari et al, 2022a ), etc. has been more successful because the amount of explained variance in present study is higher than them.…”
Section: Discussionmentioning
confidence: 91%
“…has been more successful because the amount of explained variance in present study is higher than them. Another importance of TPB in investigating forest conservation behavior was that all its variables became significant while in many studies on other fields ( Yazdanpanah and Forouzani, 2015 ; Soorani and Ahmadvand, 2019 ; Savari et al, 2022a ) all the variables were not significant, which indicates the good fit of the TPB model in explaining the behavioral intention of forest protection. The findings of this study provide new insights for policy makers to protect the environment and natural resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of social-psychological models and theories is one of the most important methods for studying conservation behavior and its preventive factors ( Turaga et al, 2010 ; Yazdanpanah et al, 2015 ; Savari and Gharechaee, 2020 ; Karimi and Saghaleini, 2021 ; Savari et al, 2022c ). Environmental psychological studies are important because they show that sustainable behavior in the environment requires individuals to internalize norms and behaviors, as incentives and constraints cannot produce sustainable manners in them ( Savari et al, 2022d ).…”
Section: Introductionmentioning
confidence: 99%